Sarcopenia severity is related to arterial stiffness and hypertension in older Korean population without underweight and obesity: population based cross-sectional study - Kim, Bokun; Kim, Gwon-Min; Huh, Up; Lee, Juhyun; Bae, Miju (Frontiers in Public Health, 2024)
Background Aging and obesity are considered causes of arterial stiffness, which triggers hypertension in the older population. However, a substantial number of older adults without obesity have hypertension, suggesting that arterial stiffness and hypertension are related to different risk factors in older adults without obesity. This cross-sectional study aimed to determine whether sarcopenia is related to arterial stiffness or hypertension in older Korean adults without underweight and obesity. Methods A total of 2,237 male and female adults in the Korea National Health and Nutritional Examination Survey who were ≥60 years and did not have underweight and obesity (18.5 ≤ body mass index <25.0 kg/m2) were involved. They were classified as moderate- (n = 276) or severe-sarcopenia (n = 528) as their sarcopenia index was 1 or 2 standard deviations lower than the mean of the young reference group. Arterial stiffness was confirmed using an estimated pulse wave velocity (ePWV) formula, and hypertension was diagnosed based on blood pressure or antihypertensive medication use. Results Arterial stiffness and systolic and diastolic blood pressure showed an increasing trend from normal to moderate-to-severe sarcopenia (p < 0.001 for both). The distribution of subjects in the highest ePWV tertile and hypertension from normal to moderate-to-severe sarcopenia showed an increasing trend (p < 0.001 for both). Subjects with moderate or severe sarcopenia were 3.545 or 8.903 times more likely to be in the highest tertile of ePWV, and those with moderate or severe sarcopenia were 2.106 or 11.725 times more likely to be hypertension (p < 0.001 for all). Conclusion Sarcopenia severity is related to arterial stiffness and hypertension in older Korean populations without underweight and obesity.